Idiopathic encapsulating peritoneal sclerosis: a case report - Gautam, Nisha; Durga, C. K. (International Surgery Journal, 2022)
Idiopathic encapsulating peritonitis sclerosis is a rare cause of small bowel obstruction. It is diagnosed by the presence of dense white fibrotic membrane encasing a part or the entire small bowel. Diagnosis is usually made intraoperatively and the treatment is usually surgical. We report a case of 16 years old female with idiopathic encapsulating peritoneal sclerosis who presented with the features of recurrent intestinal obstruction. Surgical excision of the fibrotic sac and adhesiolysis was done.